Answer:
[tex]4x + 42 = 3[/tex]
Step-by-step explanation:
Given:
[tex]\frac{2}{3}x + 7 = \frac{1}{2}[/tex]
Required
Equivalent expression without fraction
To do this, we simply multiply through by a common multiple of the denominators in the expression.
The denominators are 2 and 3
[tex]2 = 2,4,6,8,10,..[/tex]
[tex]3 = 3,6,9,12..[/tex]
So, 6 is the least common multiple.
Multiply both sides by 6
[tex]6 * (\frac{2}{3}x + 7) = \frac{1}{2} * 6[/tex]
[tex]6 *\frac{2}{3}x + 6*7 = \frac{1}{2} * 6[/tex]
[tex]\frac{12}{3}x + 42 = \frac{6}{2}[/tex]
[tex]4x + 42 = 3[/tex]
Hence, an equivalent expression.